Clinical effect of add‐on Primovist‐enhanced magnetic resonance imaging on preoperative tumor staging in hepatocellular carcinoma patients. Issue 1 (22nd June 2016) - Jin, Young‐Joo; Lee, Jin‐Woo; Kwon, Oh Sang; Jung, Young Kul; Kwon, Jung Hyun; Jang, Jeong Won; Kim, Young Seok; Kim, Tae Hun; Jeon, Yong Sun
Abstract : Background/Aims: We analyzed the incidence of change of Barcelona Clinic Liver Cancer (BCLC) stage after add‐on Primovist‐enhanced magnetic resonance imaging (MRI) in hepatocellular carcinoma (HCC) patients with Barcelona Clinic Liver Cancer stage 0 or A as determined by liver dynamic computed tomography (LDCT). Methods: A total of 166 patients enrolled prospectively between August 2012 and December 2014 were retrospectively analyzed. The rates of stage change after Primovist‐enhanced MRI and the treatment finally adopted in patients with stage change were evaluated. Results: Of the 166 patients, 24 (18.6%) had truly new HCCs. Forty‐six (27.7%) and 120 (72.3%) patients had BCLC stages 0 and A, respectively, before Primovist‐enhanced MRI, but after Primovist‐enhanced MRI, 28 (16.9%), 134 (80.7%), and 4 (2.4%) patients had BCLC stages 0, A, and B, respectively. Tumor stage changed in 22 (13.3%) patients, from 0 to A (18, 39.1%) or A to B (4, 3.3%). Conclusions: Add‐on Primovist‐enhanced magnetic resonance imaging can change BCLC stage with 13.3% in patients with BCLC 0 or A staged HCC, as determined by LDCT. J. Surg. Oncol. 2016;114:106–111 . © 2016 Wiley Periodicals, Inc.